Implementasi Model Contextual Teaching And Learning (CTL) Melalui Materi Praktik Wudhu Dalam Pembelajaran Pendidikan Agama Islam di SMP Ma’arif Seputih Raman - M. Tegas Abdillah; Irhamudin; Sayyidul Abrori (Journal of Research in Islamic Education, 2026)
This study aims to analyze the implementation of the Contextual Teaching and Learning (CTL) model in Islamic Religious Education learning through ablution practice which includes planning, implementation, and evaluation of learning. The problem of this research is that Islamic Religious Education learning is still oriented towards theoretical delivery of material so that student engagement and understanding are not optimal, especially in practical material. This study uses a qualitative approach with a descriptive type which was implemented at Ma'arif Seputih Raman Junior High School, Central Lampung Regency. The research subjects consisted of Islamic Religious Education teachers and seventh grade students selected through purposive sampling techniques. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used an interactive model that included data reduction, data presentation, and drawing conclusions with validity testing through triangulation. The results of the study showed that learning planning was carried out with ablution material with students' daily lives, learning implementation took place through direct practice that encouraged active student involvement, and evaluation was carried out authentically through assessment of practice and the learning process. The implementation of CTL through ablution practice was able to increase student engagement, understanding, and learning experiences in a more concrete and meaningful way.